"Você por acaso sabe ler?": uma análise discursiva de injúrias relativas à leitura - Cervezão, Marina Vieira (2024)
This Masters dissertation here presented, in line with the researches accomplished by the group LIRE, has as its main objective to analyze speeches about reading, more specifically, to approach the ways of expression of the ‘shame’ and ‘pride’ related to this practice, in the condition of being or not a reader, in statements that came from news of the Brazilian media as well as in personal Brazilian blogs, in which the reading is summoned as a way to stablish hierarchies between the subjects, under the way of insult, harassment and cultural and social injury (SENNAT; COBB, 1972). Over this Masters research, we have raised and analyzed statements collected along digital news texts and, also, personal Brazilian blogs that approached, even if it was briefly and accessorily, the reading, mentioned as a way at the same time to humiliate and downgrade ones and praise others. It was collected a total of ten statements, in which the use of the reading was brought up; from these, we analyzed a total of nine, which were the ones that brought statements with the intuition of the injury, the unworthiness. We believe that the low number of analyze is given for two main reasons: i) the difficulty of catching the statements in which the reading is taken as an aspect of intellectual unworthiness; and ii) the fact that this kind of statement brings up a shame to the interlocutor, preventing him of exposure. This peculiar use of the reading is part of the arguments related to the constitutive cultural gesture of our collective identity as affirms DaMatta (1990), the one from “Do you know who you are talking to?”. Because it is a practice which full exercise is restrict to just a few, it maintains along us as a way of distinction and, for this reason, it is mobilized as a “triumph” to reestablish and remind sociocultural hierarchies to that who should be “put in their correct place”. We present in this dissertation some reflection about the discursive work of the injuries related to the reading. For this analysis, we were supported by the reflections of Brazilian researchers about the reading in Brazil, such as Abreu (2001a, 2001b, 2005, 2006a, 2006b), Britto (2015), Barzotto e Britto (1998) and other member of the study group LIRE (CNPQ/UFSCar), with special attention to the works related to the emotions and the reading from Curcino (2022, 2024a) and Silva e Curcino (2022), questiong for an articulation to the considerations about the “social injury” and the dequalification of the subjects, according to the reflections of Sennet e Cobb (1972) and DaMatta (1990).